Uso de hábitat por el ñandú (Rhea americana) en un refugio de vida silvestre: Implicancias para la conservación y manejo de la especie - Bazzano, Gisela del Valle (2002)
Habitat use of the Greater Rhea (Rhea americana) in a wildlife refuge: Conservationand species management. – The habitat use of the Greater Rhea (Rhea americana) was studied from October 1997 to July 1998 in the wildlife refuge “Estancia Las Dos Hermanas”. The study area was classified in five different habitat types: grassland, agrosystems, shrubland, saline  soil, and the flooded area.Monocotyledon and dicotiledon percentages, total plant cover and average vegetation height were measured for each habitat type. Groups of rheas were more abundant during the reproductive period, in whichit was found a positive correlation between the monocotyledon percentage cover and the number of groups. Most used habitats were the grassland, paddocks with alfalfa (Medicago sativa), and the shrubland. The grassland was used mostly during reproductive period for nesting and the alfalfa paddocks were used only for foraging, particularly in the post and non-reproductive periods, while the shrubland was used forrefuge and sleeping site, more intensity during reproductive period.